Riwayat Pemberian Nutrisi pada Bayi Penderita ISPA - Siti Rofiqoh; Isyti’aroh Isyti’aroh; Windha Widyastuti; Dwi Fijianto (Jurnal Gema Keperawatan, 2023)
ARI is an acute respiratory tract infection with high morbidity rates in the pediatric group. This study aims to identify the history of nutrition with the incidence of ARI in infancy. The study conducted in Regional hospital in Pekalongan. The research design used descriptive cross-sectional. Samples obtained 75 respondents by consecutive sampling, were toddlers who were treated in that hospital in around 6 months. The research instrument used a questionnaire on the characteristics of the respondents, the history of n-utrition at the age of 0-6 months and the frequency of the incidence of ARI among baby. The data were analyzed using the Kruskal Wallis test and continued with the Post Hoc test with the Mann-Whitney Test. The results showed that the group of babies who were exclusively breastfed had the lowest average incidence of ARI compared to the group with a history of breastfeeding with formula and only formula, with a p value of 0,014. The mean rank of the incidence of ARI were lowest in the group of children with a history of exclusive breastfeeding. There was a significant difference in the average incidence of ARI in infants between groups of infants with a history of exclusive breastfeeding and breastfeeding with formula milk (p value 0,012), between groups of infants with a history of exclusive breastfeeding and formula milk only (p value 0,022). There was no significant difference between groups of infants with a history of breastfeeding with formula milk and formula milk only (p value 0.586). The results of the study can be concluded that a history of exclusive breastfeeding of infants with nutrition reduces the risk of ARI occurrence in infants.